RETRACTED: Assessment of the aridity index of various agro-climatic regions of the Republic of Azerbaijan - Shahmaliyeva Subhana Mammad; Zverkov Mikhail (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001